The shootist [videorecording (DVD)] - Wayne, John, 1907-1979; Bacall, Lauren, 1924-2014; Howard, Ron, 1954-; McKinney, Bill, 1931-2011; Stewart, James, 1908-1997; Boone, Richard; Carradine, John; Crothers, Scat Man; Lenz, Rick; Morgan, Harry, 1915-2011; North, Sheree; O'Brian, Hugh; et al. (John Wayne collection., 2006)
John Bernard Brooks, a legendary gunfighter afflicted with a terminal illness, seeks medical attention and solitudein Carson City. However, he finds himself embroiled in one last battle.